Type I Gaucher disease with exophthalmos and pulmonary arteriovenous malformation - Zhang Wei-Min; Chien Yin-Hsiu; Tang Nelson LS; Chen Chun-An; Wang Jou-Kou; Hwu Wuh-Liang (BMC, 2005)
Abstract Background Gaucher disease type I, the non-neuropathic type, usually presents in adulthood with hepatosplenomegaly. We report here an adult with type I Gaucher disease presented with unusual and severe clinical manifestations. Case presentation Hepatosplenomegaly, bone crisis and fractures occurred at early childhood, and splenectomy was performed at the age of 5. Exophthalmos with increase in retrobulbar space was noted when the patient was 30. Cerezyme infusion started at the age of 32; but unfortunately, pulmonary arteriovenous malformation with dyspnea and hypoxemia was found two years later. Gene analysis revealed V375L/L444P mutations in the β-glucocerebrosidase gene. Conclusion Although both eye and lung diseases have been associated with Gaucher disease, this is the first reported demonstration of exophthalmos and pulmonary arteriovenous malformation in the same patient. This case may therefore present an extremely severe and unusual form of type I Gaucher disease.